Financial support mechanisms for Romanian farmers beginning with 2007 - Ocnean Monica (Agrár- és vidékfejlesztési szemle, 2011)
Romanian agriculture refreshment, respectively its harmonization with the common exigencies in this field, represents a long-term process that requires the integrated application of measures specific to the general orientations of the Common Agricultural Policy. In these terms, it is necessary to improve rural infrastructure (roads and public facilities), and this process should be correlated with the creation of an attractive investment environment, with the organization of producer groups in agriculture, etc.